2022
DOI: 10.3390/foods11142064
|View full text |Cite
|
Sign up to set email alerts
|

Potential Uses of Spent Coffee Grounds in the Food Industry

Abstract: Current estimates place the amount of spent coffee grounds annually generated worldwide in the 6 million ton figure, with the sources of spent coffee grounds being classified as domestic (i.e., household), commercial (i.e., coffee houses, cafeterias and restaurants), and industrial (i.e., soluble and instant coffee industries). The majority of the produced spent coffee grounds are currently being inappropriately destined for landfills or to a form of energy recovery (e.g., incineration) as a refuse-derived fue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 143 publications
0
11
0
Order By: Relevance
“…By changing the ratio of the ethanol/water mixture as the extraction solvent, it is possible to separate a wide range of compounds. When using pure ethanol, it is predominantly lipophilic compounds that are separated, while by increasing the water content in the solvent, more phenolic type compounds can be obtained [ 18 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…By changing the ratio of the ethanol/water mixture as the extraction solvent, it is possible to separate a wide range of compounds. When using pure ethanol, it is predominantly lipophilic compounds that are separated, while by increasing the water content in the solvent, more phenolic type compounds can be obtained [ 18 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The production of food additives is a growing industry that turns over close to USD 45 billion a year [ 65 ]. SCG have been used in the preparation of baked products such as cookies and cakes as well as the production of beverages including alcoholic beverages [ 66 ]. Cookies prepared using SCG showed presence of caffeine, phenolic acids and polyphenols such as CGA [ 63 ].…”
Section: Value-adding To Scg Outside the Health Industrymentioning
confidence: 99%
“…Further, CGA extracts from coffee have been used in fried doughnuts, soymilk, wheat bread, liquid Khask, dark chocolate, yogurt and even instant coffee, which may increase the health benefits of these foods [ 67 ]. Increasing attention towards using coffee waste as a food additive will help to provide sustainable economic options to coffee farmers and reduce environmental impacts [ 66 , 68 ].…”
Section: Value-adding To Scg Outside the Health Industrymentioning
confidence: 99%
“…Besides its wide acceptance, a series of recent studies also indicated that cofee has a great inhibitory efect on obesity, diabetes [4], Alzheimer's disease [5], cardiovascular disease, infammation, cancer, and other chronic diseases [6]. Due to its excellent bioactivities, some by-products of cofee have been utilized in cosmetics, pharmaceutics, and other sectors [7,8] to replace some plant-derived extracts [9][10][11]. In particular, spent cofee grounds (SCG) present signifcant antioxidant activity and can become a prospective environmental source, which reveals their valorization in the latest studies [12][13][14].…”
Section: Introductionmentioning
confidence: 99%